How different theories of development address the relationship between the urban informal economy and poverty in the labour market - Daniel Kennedy Amoah (Discover Global Society)
Abstract The literature on informality observes a relationship between the informal economy and poverty but there is little theoretical discussion on this relationship. Despite the negative depiction of the informal economy by the modernization theory, and rather than it being replaced by the formal economy as the modernization thesis has suggested and expected, the informal economy has been growing, becoming a source of employment for many people globally. This has led to the emergence and endorsement of new representations of the informal economy. How do different theories address the relationship between the informal economy and poverty in the labour market? Through a critical review of the informal economy literature, this article discusses how various theories of development address the relationship between informality and poverty. These theories address the informality-poverty relationship based on the drivers of informality, the working conditions, and policies to facilitate the transition from the informal economy to the formal economy. Given the prevalence of the informal economy and its heterogeneous nature, policy measures should be framed around the causes, characteristics, and contexts of informal businesses.